Visualizing stellate ganglion with US imaging for guided SGB treatment: A feasibility study with healthy adults - Li, Jia; Pu, Shaofeng; Liu, Zihao; Jiang, Lixin; Zheng, Yuanyi (Frontiers in Neuroscience, 2022)
Objective As for ultrasound (US) guided stellate ganglion (SG) block, unsatisfactory curative outcomes and complications still remain. This problem could be greatly improved by identifying and monitoring SG. To the best of our knowledge, there are few reports to directly visualize SG in literature. This study explored the feasibility of detection of SG and summarized the findings of SG through US. Methods Fifty healthy adults with 100 SGs were enrolled. The size, shape, echogenicity, margin, the inferior pole of SG, the relationship between the superior pole of SG and the transverse process, the relationship between the superior pole of SG and the inferior thyroid artery, and the relationships between SG and other surrounding tissues were evaluated by US. Results The SG was identified in 79% of the participants. No significant differences were found between the right and left sides regarding thickness, cross-sectional area (CSA), and position (all p > 0.05); however, there was a significant difference in the width of the right and left sides (p < 0.05). Side was associated with SG visibility (p < 0.05), however, the gender was not (p > 0.05). A total of 42% of SGs were oval-shaped. All SGs were hyperechogenic and had an ill-defined margin. In fact, 63% of SGs were located in the C7 transverse process level, 77% of SGs were located under the inferior thyroid artery, and all of these SGs were located lateral to the thyroid and medial to the anterior scalene muscle and the vagus nerve. Conclusion Our preliminary study demonstrates that US imaging provides the capability of detecting SG. This may be helpful in minimizing complications and improving the accuracy of US-guided SG block.